Benzo(a)pyrene in Europe: Ambient air concentrations, population exposure and health effects. (July 2016) - Guerreiro, C.B.B.; Horálek, J.; de Leeuw, F.; Couvidat, F.
Abstract: This study estimated current benzo(a)pyrene (BaP) concentration levels, population exposure and potential health impacts of exposure to ambient air BaP in Europe. These estimates were done by combining the best available information from observations and chemical transport models through the use of spatial interpolation methods. Results show large exceedances of the European target value for BaP in 2012 over large areas, particularly in central-eastern Europe. Results also show large uncertainties in the concentration estimates in regions with a few or no measurement stations. The estimation of the population exposure to BaP concentrations and its health impacts was limited to 60% of the European population, covering only the modelled areas which met the data quality requirement for modelling of BaP concentrations set by the European directive 2004/107/EC. The population exposure estimate shows that 20% of the European population is exposed to BaP background ambient concentrations above the EU target value and only 7% live in areas with concentrations under the estimated acceptable risk level of 0.12 ng m −3 . This exposure leads to an estimated 370 lung cancer incidences per year, for the 60% of the European population included in the estimation. Emissions of BaP have increased in the last decade with the increase in emissions from household combustion of biomass. At the same time, climate mitigation policies are promoting the use of biomass burning for domestic heating. The current study shows that there is a need for more BaP measurements in areas of low measurement density, particularly where high concentrations are expected, e.g. in Romania, Bulgaria, and other Balkan states. Furthermore, this study shows that the health risk posed by PAH exposure calls for better coordination between air quality and climate mitigation policies in Europe. Highlights: We estimate current benzo(a)pyrene (BaP) concentration levels in Europe. We estimate the European population exposure to BaP. BaP exposure leads to more than 370 lung cancer incidences per year in Europe. The main BaP emission sector is household combustion and its emissions increase. Better coordination between air quality and climate mitigation policies is needed. Abstract : A model was developed for estimating background benzo(a)pyrene concentrations in Europe, allowing the estimation of population exposure and health impacts for 60% of the European population.